Anti-diabetic and anti-hyperlipidemic properties of Capparis spinosa L.: In vivo and in vitro evaluation of its nutraceutical potential. (August 2017) - Mollica, Adriano; Zengin, Gokhan; Locatelli, Marcello; Stefanucci, Azzurra; Mocan, Andrei; Macedonio, Giorgia; Carradori, Simone; Onaolapo, Olakunle; Onaolapo, Adejoke; Adegoke, Juliet; Olaniyan, Marufat; Aktumsek, Abdurrahman; et al.
Highlights: Antidiabetic and antihyperlipidemic effects of Capparis spinosa from Lipari Island. Extractions of buds, salty buds, leaf by different techniques. HLPC-DAD analysis. Enzyme inhibition tests on α-amylase and α-glucosidase. Histophysiology modifications of pancreas, liver, kidney. Abstract: In this study, the nutraceutical potential of Capparis spinosa L . for the treatment of hyperglycemic states has been thoroughly investigated. A series of in vivo and in vitro tests have been conducted on fresh leaf, buds and salty buds (24 h desalted) processed to dry powder. 60% MeOH/H2 O extracts were obtained for HPLC analysis and for α-amylase and α-glucosidase inhibition tests. To estimate the in vivo anti-diabetic effect, dry powders of C. spinosa leaf and buds were orally administered to streptozocin-induced diabetic rats over a period of 28 days. At the end of the experiment, animals were sacrificed, blood taken for assessment of lipid profile and liver/kidney biochemistry while section of the pancreas, liver and kidneys were processed for general histology. Results showed that the regular administration of C. spinosa leaf or buds normalized all the biochemical parameters and reversed the liver/kidney injury with variable degrees of organ protection.